7
$\begingroup$

I'm dealing with another silly problem, now with radicals, I've the equation:

$(\frac{1}{9})^x = \sqrt{27}$

Working on it:

$9^{-x} = 27^{\frac{1}{2}}$

$9^{-x} = 3^{3\times\frac{1}{2}}$

$9^{-x} = 3^{\frac{3}{2}}$

$3^{-3x} = 3^{\frac{3}{2}}$

with exponents:

$-2x = \frac{3}{2}$

$x = \frac{3}{2} \cdot (-\frac{1}{2})$

$x = -\frac{3}{4}$

But it's not compatible, where's the mistake ?

Edit

Sorry, it was typo, it's fixed now, but I'm still unable to prove that:

$\dfrac{1}{9}^{-\dfrac{3}{4}} = \sqrt{27}$

How could I do that ?

$\endgroup$
  • 5
    $\begingroup$ Looks like you have a typo on the line before "with exponents", but it looks like the only real mistake is in the final multiplication. $\endgroup$ – Mike Mar 27 '12 at 0:40
  • $\begingroup$ (+1) for work shown. @Mike: You should make that an answer! $\endgroup$ – The Chaz 2.0 Mar 27 '12 at 0:42
2
$\begingroup$

To answer the new question, you may want to manipulate the exponent in the same fashion you used to get the answer in the first place.

$(\frac19)^{-\frac34}=[(\frac19)^{-1}]^\frac34=9^\frac34=(9^\frac12)^\frac32=3^\frac32=(3^3)^\frac12=\sqrt{27}$

$\endgroup$
  • $\begingroup$ Thank you so much, I'm so bad working with rationals, thanks; $\endgroup$ – aajjbb Mar 28 '12 at 2:59
6
$\begingroup$

You made a mistake on one of the last lines (also, in the line before "with exponents" it's $3^{-2x}=3^{\dfrac{3}{2}}$ but I think it's a typo). When you have $x=-\dfrac{1}{2}.\dfrac{3}{2}$ the product should be $x=-\dfrac{3}{4}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.